Protein Extraction From FFPE Kidney Tissue Samples: A Review of the Literature and Characterization of Techniques - García-Vence, Maria; Chantada-Vazquez, Maria del Pilar; Sosa-Fajardo, Ana; Agra, Rebeca; Barcia de la Iglesia, Ana; Otero-Glez, Alfonso; García-González, Miguel; Cameselle-Teijeiro, José M.; Nuñez, Cristina; Bravo, Juan J.; Bravo, Susana B. (Frontiers in Medicine, 2021)
Most tissue biopsies from patients in hospital environments are formalin-fixed and paraffin-embedded (FFPE) for long-term storage. This fixation process produces a modification in the proteins called "crosslinks", which improves protein stability necessary for their conservation. Currently, these samples are mainly used in clinical practice for performing immunohistochemical analysis, since these modifications do not suppose a drawback for this technique; however, crosslinks difficult the protein extraction process. Accordingly, these modifications make the development of a good protein extraction protocol necessary. Due to the specific characteristics of each tissue, the same extraction buffers or deparaffinization protocols are not equally effective in all cases. Therefore, it is necessary to obtain a specific protocol for each tissue. The present work aims to establish a deparaffinization and protein extraction protocol from FFPE kidney samples to obtain protein enough of high quality for the subsequent proteomic analysis. Different deparaffination, protocols and protein extraction buffers will be tested in FFPE kidney samples. The optimized conditions will be applied in the identification by LC-MS/MS analysis of proteins extracted from 5, 10 and 15 glomeruli obtained through the microdissection of FFPE renal samples.